2009
DOI: 10.1096/fasebj.23.1_supplement.733.2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of Nigella sativa and bees' honey on hepatotoxicity induced by administration of sodium nitrite and sunset yellow

Abstract: BackgroundThe study was conducted to shed the light on adverse effects of food additive such as sodium nitrite (NaNO2; as preservative) and sunset yellow (as color) on the rat liver. Furthermore, the study was extended to show the protective role of Nigella sativa (black seed) and bees' honey in modulating the toxic effects induced by these additives.Methods‐resultsData show that the administration of NaNO2 and sunset yellow caused significant increase in serum and liver total lipids, total cholesterol, riglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Our study revealed that the administration of the combination of BSO and honey in variety provides a better effect than a single treatment of BSO or honey. This result is in line with a study conducted by El-Kholy et al, a better protective effect on the liver was obtained after the combination of BSO and honey was given (20). This study was an experimental study, which was carried out by comparing histopathological preparations between the normal control group, negative control group, and the exposure group so that the types of damage that occurred could be compared.…”
Section: Discussionsupporting
confidence: 86%
“…Our study revealed that the administration of the combination of BSO and honey in variety provides a better effect than a single treatment of BSO or honey. This result is in line with a study conducted by El-Kholy et al, a better protective effect on the liver was obtained after the combination of BSO and honey was given (20). This study was an experimental study, which was carried out by comparing histopathological preparations between the normal control group, negative control group, and the exposure group so that the types of damage that occurred could be compared.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, it succeeded to induce an improvement in kidney function. Our results are in agreement with previous data reporting that N. sativa and licorice have a wide margin of safety (EL-Kholy et al, 2009, AL Ameen et al, 2011. Effect of Nigella stevia and Licorice extract on histological characteristics of Ovary in rats.. Light microscopic examination of ovarian sections of the control group stained with hematoxylin and eosin showed the normal histological structure of the ovary with normal cortical and medullary regions, including primary and secondary follicles (Fig.…”
Section: Gross Chemical Composition and Caloric Value Of Nigella Stev...supporting
confidence: 92%
“…In another study carried out over rats, it was found that stomach lesions of the subjects fed with daily honey diet (Zanini et al, 2014). In the use of bee honey with the seeds of black cumin (Nigella sativa L.), it was found that it has protective effects upon hepatoxicity, oxidative stress and carcinogenesis (El-Kholy et al, 2009). However, there could be some reactions varying from simple cough to anaphylaxis in allergic bodies with the consumption of uncontrollably produced honeys and it is necessary to warn in this sense (Martos et l., 2008).…”
Section: Effects Of Honey On Healthmentioning
confidence: 99%